Understanding of Taxation, Utilization of Accounting Technology and Use of E-filling on Taxpayer Compliance with Internet Understanding as Moderation - Ayem, Sri; Rahmadani, Yasminia Eka (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the effect of understanding taxation, utilization of accounting information technology and the use of e-filling on taxpayer compliance with internet understanding as moderation. This research uses quantitative methods with the data source used, namely primary data. The population in this study are taxpayers who have NPWP and are registered at KPP Pratama. The data analysis technique uses multiple linear regression and moderated regression analysis (MRA) using SPSS 25. The results showed that the influence of taxation, accounting information technology and the use of e-filling had a positive and significant effect. Internet understanding moderates the understanding of taxation and the use of e-filling. However, internet understanding is unable to moderate the use of accounting information technology. The results of this study are expected to help improve taxpayer compliance with their obligations as taxpayers.